Surface colour variation of Papaya fruits with maturity - Amarasinghe, D.I.; Sonnadara, D.U.J. (My University, 2009)
Surface colour considered as a quality parameter change with the maturity of fruits. Many unripe fruits initially show greenish surface colour which gradually changes to yellow colour when they mature. The change of colour patterns is similar within each fruit category. The consumer often judges the ripeness of the fruits by its colour. If the relationship between the surface colour of a fruit category and the maturity can be determined, development of electronic devices capable of sorting fruits automatically depending on the level of ripeness is a possibility. This is also useful for grading fruits when they are being harvested. In this work, by applying image processing techniques colour change with the maturity of Papaya fruits was studied. The commonly available papaya variety ‘Red Lady’ was selected to carry out this work because they show clear colour variation during the ripening period. RGB and OHTA colour spaces based image segmentation algorithms were developed to detect yellow colour regions in papaya fruits. A normalization technique was applied to reduce systematic bias due to the surrounding light condition in the RGB space. Results show a non-linear increase in the surface yellow colour with the age of the fruits. Preliminary results show that normalizing technique can help to reduce this systematic bias.
Keywords: Image processing; Colour detection